Influence of wire electrical discharge machine cutting parameters on the magnetization characteristics of electrical steel laminations - Robert F.; Prince A A.; Fredo A R J. (My University, 2025)
This paper presents the influence of wire electrical discharge machine (WEDM) cutting parameters on the magnetization characteristics of electrical steel. The demand for electrical steel keeps increases because of the high demand of electrical motor and transformers for electric vehicle and smart grid applications. The magnetization characteristics of the laminated steel used in these machines have dominates the performance of these machines. The cuttings methods and cutting parameters have huge role in deciding the magnetization characteristics. In this work, WEDM is used to cut the electrical steel in to small pieces. The cutting parameters such as current, feed rate and on-time of WEDM are varied by keeping two of these parameters fixed and one varied. From the electrical steel sheet, 18 sample small electrical steel pieces are obtained at various cutting parameters of WEDM. The magnetic field - magnetization characteristics are obtained using vibrating sample magnetometer (VSM). This analysis shows that higher current, lower on-time and higher feed rate is providing higher magnetization. © 2022 Elsevier Ltd. All rights reserved.